Technical report: mathematical modelling on the control of measles by vaccination in Malaysia / Siti Fathiah Amanina Ishak, Siti Noor Intanbaizura Mohd Aripin and Siti Sarah Fahana Kamaruddin - Ishak, Siti Fathiah Amanina; Mohd Aripin, Siti Noor Intanbaizura; Kamaruddin, Siti Sarah Fahana (2017)
The SEIR model for measles disease transmission is discussed here. The host (human) population is divided into four compartments: susceptible, exposed, infected, and recovered. The interest here is to deduce SEIR model to predict the transmission of measles in Malaysia. SEIR model is used to investigate the transmission of measles against vaccination used and to find the effective reproductive number in presence of vaccination, Rp and basic reproductive number, Ro. Based on the parameter values in Table 3.4 and Table 3.5, the epidemic conditions or also known as basic reproductive number, Ro (97) was calculated where the value is Ro=2.4180 which is greater than unity, 1. The value obtained implies that there is will be an epidemic for the measles virus in the population. Then, the data and parameter values were substituted into Rp (82) where the value obtained is Rp = 0.6080. The value of Rp shows that it is smaller than 1 which means the epidemic for the measles virus can be eliminated by increasing the mass vaccination among the individuals in the population. The data is obtained for the year 2015. The SEIR model is solved by using command from maple software. From the observations, the higher the dosage of vaccination used, the higher the number of recovered population. Other than that, in order to increase number of recovered individuals, the dosage of vaccination should be increase year by year.